Transesterifikasi Minyak Sawit Off-Grade Menjadi Biodiesel Menggunakan Katalis CaO Yang Diimpregnasi Dengan Limbah Serbuk Besi - Muhammad Rahman; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Off-grade oil is a raw material for biodiesel that has ALB levels> 2% so that the production of biodiesel made by two stage reaction, the esterification and transesterification. In general, biodiesel is produced using homogeneous catalysts. Homogeneous catalysts can be replaced by a heterogeneous catalyst. CaO catalyst has a high alkalinity but has shortcomings in the process of separation of the reaction products. Waste iron powder can be used as a support and to provide a catalyst Ca2Fe2O5 metal forming properties. This study aims to create a catalyst that has a high alkalinity and metallic, and study the performance of the catalyst in the transesterification reaction of palm oil off-grade. Esterification process were reacted at 60°C with a mole ratio of oil: methanol of 1:12 and 1% H2SO4 catalyst -b. The esterification reaction can reduce levels of ALB from 12.47% to 0.36%. Transesterification is done by varying the mole ratio of oil: methanol in a row is 1: 6, 1: 8 and 1:10, the amount of catalyst modification 1% -b, -b 2%, 3% -b, a reaction temperature of 50°C, 60°C, 70°C, and the reaction time 2 hours. Processing data using Response Surface Area (RSM), the amount of attack using Central Composite Design (CCD). The resulting yield ranging from 23.19% to 52.34%. The highest yield obtained at 70°C with a mole ratio of oil: methanol of 1:10 and the amount of catalyst Ca2Fe2O5 1%-b. Biodiesel characteristics such as density, kinematic viscosity, acid number and flash point are in accordance with the standards of Indonesian biodiesel. The most significant process conditions to yield biodiesel is the ratio of the mole ratio of oil: methanol and the amount of catalyst.Keywords : Biodiesel, Catalyst, Off-grade Palm Oi, Transesterification, Wasted Iron